2016
DOI: 10.5014/ajot.2016.70s1-po1088
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems in Children With Autism Spectrum Disorder and in Their Caregivers

Abstract: Date Presented 4/7/2016 This descriptive study found relationships between the sleep problems in children with autism spectrum disorder and the sleep problems of their caregivers. Interventions to improve child sleep must consider the genetic and environmental factors that contribute to sleep quality in the parent–child dyad. Primary Author and Speaker: Maureen Russell Contributing Authors: Carol Baldwin, Stuart Quan, Darya McClain, Christopher Smith, Nicole Matthews Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Sleep impaired caregivers are also more likely to report psychological distress (Richdale & Baglin, 2015), and care recipients of psychologically distressed caregivers find adjusting to their illness more challenging (Dockerty et al, 2000). Moreover, caregivers' and care recipients' sleep disturbances tend to be highly correlated (Russell et al, 2016), and greater sleep disturbances in children with ASD predict increased difficulties with daytime functioning (Lambert et al, 2016). Other studies also found quality of life for the child with DD, particularly in domains of social, emotional and physical functioning, to be closely related to the physical health of the care provider (Lovell, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep impaired caregivers are also more likely to report psychological distress (Richdale & Baglin, 2015), and care recipients of psychologically distressed caregivers find adjusting to their illness more challenging (Dockerty et al, 2000). Moreover, caregivers' and care recipients' sleep disturbances tend to be highly correlated (Russell et al, 2016), and greater sleep disturbances in children with ASD predict increased difficulties with daytime functioning (Lambert et al, 2016). Other studies also found quality of life for the child with DD, particularly in domains of social, emotional and physical functioning, to be closely related to the physical health of the care provider (Lovell, 2018).…”
Section: Discussionmentioning
confidence: 99%